Res publica constituta : Actium, Apollo and the accomplishment of the triumviral assignment - Lange, Carsten Hjort (2008)
This thesis will focus on the battle of Actium and the ways in which the Caesarian regime represented and commemorated this conflict and turned it to Octavian/Augustus's purpose. It will be argued that Actium was relatively more important than Alexandria in the ideology of the regime, but at the same time that the two battles must be understood together, as part of the accomplishment of the assignment of the triumvirate (constituting the res publica to order and ending the civil war). The focus will thus be on the period between 43-27 BC.